Dexterous Route for Synthesis of Hollow Spherical ZnO and ZnO‐Ag Nanocomposite with Superior Photocatalytic Ability. Issue 19 (20th May 2019) - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree
Abstract: Hollow spherical ZnO and hollow ZnO−Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO−Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV‐Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity. Abstract : Describing an excellent route to synthesize hollow ZnO which can be conveniently converted to ZnO−Ag nanocomposite. This composite has demonstrated photocatalysis for MB dye degradation depending on the percentages of Ag loaded on hollow ZnO matrix. An optimum percentage of Ag on ZnO is determined where the composite has achieved maximum degradation efficiency. The hollow nature of matrix (ZnO) has found to increase the efficiency when compared to commercial ZnO used as matrix for ZnO−Ag composite.